2020
DOI: 10.2147/copd.s268905
|View full text |Cite
|
Sign up to set email alerts
|

<p>First-Line Treatment with Tiotropium/Olodaterol Improves Physical Activity in Patients with Treatment-Naïve Chronic Obstructive Pulmonary Disease</p>

Abstract: Background Comparative effects on physical activity of mono and dual bronchodilators remain unclear in patients with treatment-naïve chronic obstructive pulmonary disease (COPD). We sought to compare the changes in physical activity before and after tiotropium and tiotropium/olodaterol treatment in treatment-naïve COPD patients. Methods A prospective, multicenter, randomized, open-labeled, and parallel interventional study was conducted. Eighty Japanese patients with tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 36 publications
(38 reference statements)
2
11
0
1
Order By: Relevance
“…Indeed, a prospective, observational study of 130 COPD patients showed that ECM CSA is correlated with clinical parameters of COPD and more correlated with all-cause mortality than PM CSA 20 . In addition, a longitudinal, 10-year observational study showed that loss of ECM CSA , but not PM CSA , significantly increased the hazard ratio of mortality 21 , because physical activity is the strongest predictor of the prognosis of COPD patients 3 , and sedentary behavior, which affects the anti-gravity muscles, is particularly important in COPD 29,30 ; thus, anti-gravity muscles might contribute to exercise tolerance in patients with COPD, as seen in the present study.…”
Section: Discussionsupporting
confidence: 61%
“…Indeed, a prospective, observational study of 130 COPD patients showed that ECM CSA is correlated with clinical parameters of COPD and more correlated with all-cause mortality than PM CSA 20 . In addition, a longitudinal, 10-year observational study showed that loss of ECM CSA , but not PM CSA , significantly increased the hazard ratio of mortality 21 , because physical activity is the strongest predictor of the prognosis of COPD patients 3 , and sedentary behavior, which affects the anti-gravity muscles, is particularly important in COPD 29,30 ; thus, anti-gravity muscles might contribute to exercise tolerance in patients with COPD, as seen in the present study.…”
Section: Discussionsupporting
confidence: 61%
“…Clinical trial evidence has consistently demonstrated greater efficacy in lung function, symptom and exacerbation outcomes with LAMA/LABA therapy versus monotherapy, with a similar safety profile [42,45,47,[53][54][55][56][57][58][59][60][61][62][63][64][65]. Crucially, several recent studies have suggested that these treatment differences are also apparent in maintenance-naïve and ICS-free COPD populations, who more closely resemble those at first presentation in clinical settings [45,[58][59][60][61][62][63][64][65]. There is also evidence that LAMA/LABA combination treatments prevent future disease deteriorations, measured by CID events [41,42,45,47,59].…”
Section: Discussionmentioning
confidence: 99%
“…There is little evidence of the impact of dual therapy on physical activity in maintenance-naïve patients. The SCOPE study in Japanese patients found no significant difference in 6-min walk distance, daily number of steps or changes in the duration of physical activity in patients treated with TIO/OLO versus TIO [65].…”
Section: Symptom and Health Status Outcomesmentioning
confidence: 93%
See 2 more Smart Citations